An Aboriginal Australian Genome Reveals Separate Human Dispersals into Asia - Rasmussen, M.; Guo, X.; Wang, Y.; Lohmueller, K.; Rasmussen, S.; Albrechtsen, A.; Skotte, L.; Lindgreen, S.; Metspalu, M.; Jombart, T.; Kivisild, T.; Zhai, W.; et al. (The American Association for the Advancement of Science, 2011)
We present an Aboriginal Australian genomic sequence obtained from a 100-year-old lock of hair donated by an Aboriginal man from southern Western Australia in the early 20th century. We detect no evidence of European admixture and estimate contamination levels to be below 0.5%. We show that Aboriginal Australians are descendants of an early human dispersal into eastern Asia, possibly 62,000 to 75,000 years ago. This dispersal is separate from the one that gave rise to modern Asians 25,000 to 38,000 years ago. We also find evidence of gene flow between populations of the two dispersal waves prior to the divergence of Native Americans from modern Asian ancestors. Our findings support the hypothesis that present-day Aboriginal Australians descend from the earliest humans to occupy Australia, likely representing one of the oldest continuous populations outside Africa